1988
DOI: 10.1111/j.1834-7819.1988.tb04181.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of temporomandibular joint dysfunction among patients wearing complete dentures

Abstract: This study investigates the prevalence of temporomandibular joint dysfunction among complete denture wearers and relates the incidence ta various features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
3

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
4
18
0
3
Order By: Relevance
“…Alguns estudos -Bontempo, Zavanelli 5 , Raustia et al 16 , Zissis et al 17 e Mesko et al 18 -concordam com os resultados atuais e afirmam que os pacientes que usavam as mesmas próteses totais havia mais tempo (anos), assim como aqueles que não trocaram suas próteses totais periodicamente, apresentaram mais sinais de DTM do que os pacientes que as trocaram com maior frequência.…”
Section: Discussionunclassified
“…Alguns estudos -Bontempo, Zavanelli 5 , Raustia et al 16 , Zissis et al 17 e Mesko et al 18 -concordam com os resultados atuais e afirmam que os pacientes que usavam as mesmas próteses totais havia mais tempo (anos), assim como aqueles que não trocaram suas próteses totais periodicamente, apresentaram mais sinais de DTM do que os pacientes que as trocaram com maior frequência.…”
Section: Discussionunclassified
“…Studies have reported that loss of teeth, unilateral chewing patterns, and bruxism were associated with nonphysiological overloading of the remaining structures and that this excessive loading aggravated existing temporomandibular joint arthritis and increased the risk of arthrosis beyond what was expected with normal aging (Mongini, 1972;Budtz-Jorgensen et al, 1985;Christensen and Ziebert, 1986;Agerberg, 1988;Zissis et al, 1988;Mercado and Faulkner, 1991). Correlations have also been found between degree of joint dysfunction and loss of natural posterior supporting teeth (Choy and Smith, 1980;Budtzlorgensen et al, 1985;.…”
Section: (2) Loss Of Posterior Teethmentioning
confidence: 99%
“…Approximately 15 to 20% of complete denture wearers have symptoms consistent with degenerative joint disease, including joint sounds, restricted movement, and reduced bite force (Choy and Smith, 1980;Magnusson, 1982;Agerberg, 1988;Tervonen and Knuuttila, 1988;Zissis et al, 1988). Edentulous individuals who do not wear dentures have an extremely low incidence (approximately 5%) of joint disorders (Wilding and Owen, 1987).…”
Section: (3) Edentulism and Denture Wearingmentioning
confidence: 99%
“…Gynther to be almost as prevalent in CD wearers as in individuals with natural dentition, 16,17 while others found CD with an increased joint dysfunction symptoms in patients wearing CD than the individuals with natural dentition. 18 Some researchers have also found lesser prevalence of TMJ dysfunction in CD wearers and contributed this finding to the fact that such individuals have reduced maximum opening levels and five to six times lesser bite force than in dentate patients, so from time to time, they surpass their tissue resilience and flexibility leading to lesser prevalence of TMD.…”
Section: 11mentioning
confidence: 98%